Genetic variability and QTL mapping of winter survivability and leaf firing in African bermudagrass. Issue 6 (26th October 2022) - Yu, Shuhao; Schoonmaker, Ashley N.; Yan, Liuling; Hulse‐Kemp, Amanda M.; Fontanier, Charles H.; Martin, Dennis L.; Moss, Justin Q.; Wu, Yanqi Q.
Abstract: Turf‐type bermudagrass is susceptible to winterkill when grown in transition zone climates. Minimizing water use in turfgrass management is of societal significance. African bermudagrass ( Cynodon transvaalensis Burtt‐Davy) has been extensively used to cross with common bermudagrass ( C. dactylon Pers. var. dactylon ) in the creation of F1 hybrid cultivars. Little information regarding the molecular basis of winter survivability and drought resistance in African bermudagrass is available. Accordingly, the objectives of this study were to quantify genetic variability and identify quantitative trait loci (QTL) associated with winter survivability traits (spring greenup, SG; spring greenup percent green cover, SGPGC; winterkill, WK), and leaf firing (LF) in African bermudagrass. A total of 109 first‐generation self‐pollinated (S1 ) progeny of 'OKC1163' were evaluated in a field trial in a randomized complete block design with three replications for four seasons. Significant genetic variation existed for all the traits examined, and the broad‐sense heritability estimates ranged from .36 to .54 for the winter survivability traits and .80 for LF. Ten QTL were identified for winter survivability traits and two for LF based on a preexisting high‐density linkage map, which was aligned, reoriented, and renamed as to a recently published reference genome. Seven of 12 QTL were consistently identified at least in 2 yr. The colocation of two QTL, one for winter survivability and another for LF, suggests the possibility of improving both traits together. Findings provide new insights to genetic control of winter survivability traits and LF and contribute genetic resources for marker‐assisted selection in turf‐type bermudagrass improvement. Core Ideas: Winter survivability traits and LF are critical to the development of new turf‐type bermudagrass cultivars. One hundred and nine S1 African bermudagrass progeny were characterized for winter survivability and LF. We identified 10 QTL associated with winter survivability and two QTL for LF.